Educação e desenvolvimento da criança na primeira infância: o campo das responsabilidades - Faria, Alessandra de Carvalho [UNESP]; Palmeira, Cíceran Martins [UNESP]; Angotti, Maristela [UNESP] (My University, 2013)
The new educational context requires the prospect of a more playful and pedagogic practices more flexible, and that meets promote child development, which includes the child in her singularity and allows her to read display that features the world, that stimulates exercise and allow the creative act that respects the feelings and emotions she has, which values ​​the different forms of infantile expression. The child needs and is entitled to promote his integral development potential. Therefore, it is necessary to have professional commitment to promote a quality educational services for children.

O novo contexto educacional requer a perspectiva de um atendimento mais lúdico e de práticas pedagógicas mais flexíveis, que atenda e promova o desenvolvimento infantil, que compreenda a criança em sua singularidade e que permita a ela apresentar seu olhar e leitura de mundo, que estimule e permita o ato criativo, que respeite sentimentos e emoções, que valorize as diferentes formas de expressão infantil. A criança precisa e tem por direito a promoção de seu desenvolvimento integral, potencial. Para tanto, sendo necessário o compromisso profissional no investimento de um atendimento educacional de qualidade.
Education and development of children at the first childhood: the field of responsibilities
Keywords: Nursery; Pre-School; Teaching practice; Formation of educators; Creche; Pré-escola; Prática pedagógica; Formação de educadores